DEVELOPMENT OF KUMAL (KUIS ANIMALIA) GAME EVALUATION TOOL FOR SMA/MA CLASS X - Yanggi Lutfian Fathoni; Dian Puspita Anggraini; Devita Sulistiana (JARES (Journal of Academic Research and Sciences), 2023)
Biological evaluation tools are very important. The current reality is that biology evaluation tools are rarely used in learning because of limited tools, materials and time. One of the efforts made is to develop a computer/PC-based KUMAL (Kuis Animalia) game application. The aim is to determine the feasibility of the KUMAL game developed as a learning evaluation tool on animalia material. The research was conducted using Research and Development (R&D) research and development methods. The samples in this study were 3 material experts, 3 media experts and 3 IT experts. The validation results from this study are 84% with a very feasible category from the material validator, 83% with a very feasible category from the media validator and 83% with a very feasible category from the IT validator. The conclusion of this study is that the KUMAL game is feasible to be used as an evaluation tool for biology learning in animalia material for class X SMA/MA.